EVALUATION OF ANTI-FATIGUE ACTIVITY OF FLAVONOIDS FROM TARTARY BUCKWHEAT IN MICE - Miao, Fusheng; Wu, Di; Ni, Guichao (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Flavonoids are the major biological activities components of tartary buckwheat which has multifunctional bioactivities. However, there are a limited number of studies on the effect of flavonoids from tartary buckwheat (TBF) on physical fatigue at present. This study aimed to investigate the anti-fatigue activity of TBF in mice. Materials and Methods: The mice were divided into four groups: control (C), low-dose TBF-treated (LFT), middle-dose TBF-treated (MFT) and high-dose TBF-treated (HFT). The treated groups received TBF (100, 200 and 400 mg/kg), while the control group received physiological saline. After 28 days’ treatment, the mice performed exhaustive running exercise on the treadmill, along with the measure of exhaustive running times, blood lactic acid (BLA), serum urea nitrogen (SUN), serum creatine kinase (SCK), liver glycogen, superoxide dismutase (SOD), glutathione peroxidase (GPx) and catalase (CAT). Results: TBF prolonged the exhaustive running time of the mice. It sub-served to remove the accumulated products of metabolism by decreasing the levels of BLA and SUN. It ameliorated the muscle damage by decreasing the SCK levels. It improved the metabolic control of exercise and activated the energy metabolism by increasing the liver glycogen contents, as well as improving endogenous cellular antioxidant enzymes in mice by increasing the SOD, GPx and CAT activities. Conclusion: TBF has significant anti‑fatigue activity.